Image-guided percutaneous sclerotherapy of venous malformations of the head and neck: clinical and MR-based volumetric mid-term outcome - Vollherbst, Dominik; Gebhart, Philipp; Kargus, Steffen; Burger, Astrid; Kühle, Reinald; Günther, Patrick; Hoffmann, Jürgen; Bendszus, Martin; Möhlenbruch, Markus Alfred (PLOS ONE, 2020)
Objective To report the clinical and MRI-based volumetric mid-term outcome after image guided percutaneous sclerotherapy (PS) of venous malformations (VM) of the head and neck. Methods A retrospective analysis of a prospectively maintained database was performed, including patients with VM of the head and neck who were treated with PS. Only patients with available pre- and post-interventional MRI were included into this study. Clinical outcome, which was subjectively assessed by the patients, their parents (for paediatric patients) and/or the physicians, was categorized as worse, unchanged, minor or major improvement. Radiological outcome, determined by MRI-based volumetric measurements, was categorized as worse (>10% increase), unchanged (≤10% increase to <10% decrease), minor (≥10% to <25% decrease), intermediate (≥25% to <50% decrease) or major improvement (≥50% decrease). Results Twenty-seven patients were treated in 51 treatment sessions. After a mean follow-up of 31 months, clinical outcome was worse for 7.4%, unchanged for 3.7% of the patients, while there was minor and major improvement for 7.4% and 81.5%, respectively. In the volumetric imaging analysis 7.4% of the VMs were worse and 14.8% were unchanged. Minor improvement was observed in 22.2%, intermediate improvement in 44.4% and major improvement in 11.1%. The rate of permanent complications was 3.7%. Conclusion PS can be an effective therapy to treat the symptoms of patients with VMs of the head and neck and to downsize the VMs. MRI-based volumetry can be used to objectively follow the change in size of the VMs after PS. Relief of symptoms frequently does not require substantial volume reduction.